Clément Marot and religion: a reassessment in the light of his Psalm paraphrases - Wursten, Dick (Brill's series in church history, 2010)
A far-reaching analysis of Clment Marots poetry (mainly his Psalm paraphrases) shows that this poet was much more than a frivolous court poet; he was touched by the humanist yearning to restore old texts (in this case the Jewish Psalter) to their ori